2010
DOI: 10.1583/10-3065.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Common Carotid Artery Dissection Via the Superficial Temporal Artery

Abstract: In selected cases, the superficial temporal artery may represent a valid alternative approach for the endovascular treatment of short CCA dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Retrograde EVT via the superficial temporal artery instead of the femoral artery was performed because of a partially compromised aortobifemoral bypass graft. 10 A deformed arch anatomy caused by total arch replacement or a stented elephant trunk implantation may prevent a conventional antegrade approach for intervention because of additional challenges. For example, the study by Tsai and Shen reported a patient who developed symptomatic left CCA restenosis 2 weeks after total arch rerouting and elephant trunk repair for an acute aortic dissection with left CCA malperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde EVT via the superficial temporal artery instead of the femoral artery was performed because of a partially compromised aortobifemoral bypass graft. 10 A deformed arch anatomy caused by total arch replacement or a stented elephant trunk implantation may prevent a conventional antegrade approach for intervention because of additional challenges. For example, the study by Tsai and Shen reported a patient who developed symptomatic left CCA restenosis 2 weeks after total arch rerouting and elephant trunk repair for an acute aortic dissection with left CCA malperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, there have been new reports on iatrogenic carotid dissections following surgical repair of aortic dissection 3,8,9 or carotid endarterectomy (CEA). 10 Here, we report a rare case of dissections in the innominate and left common carotid arteries after a total arch replacement that was successfully treated with open retrograde EVT reconstruction in the left common carotid artery (CCA). We also address previous similar reports.…”
mentioning
confidence: 99%
“…3,9,10 Physiatrist of our Institution evaluated the FMI for monitoring functional improvements after rehabilitation treatment. This validated tool 14,15 has high internal consistency and adequate discriminative capabilities for functional impaired patients. When the patient was admitted to our Institution, her motor items FIM score was 46/91 and 77/91 at final discharge.…”
Section: Discussionmentioning
confidence: 99%
“…913 In difficult CAS cases, the STA has been used for this accessory access but always via surgical exposure. 36 However, ultrasound-guided percutaneous arterial access is a relatively simple procedure, and our technique for the STA is similar to that used in other small vessels, such as the radial or tibial artery. The STA, with a diameter (2.73± 0.51 mm) comparable to that of the radial artery, 14 is usually superficial and easy to visualize on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The superficial temporal artery (STA) has been previously used as an additional access for a through-and-through guidewire to facilitate CAS in challenging situations. 36 Access to the STA has been obtained with a surgical cutdown in the past, but we describe an entirely percutaneous, ultrasound-guided approach to the STA to facilitate transfemoral CAS.…”
mentioning
confidence: 99%